Guide through it will be appreciated, thanksSimplify:
(x^2 - y^2 - 2x - 2y) X (xy-3y^2)
(x^2 - 2xy - 3y^2) X (y-x+2)
$\displaystyle \frac{(x^2 - y^2 - 2x - 2y)(xy - 3y^2)}{(x^2 - 2xy - 3y^2)(y - x + 2)}$
Take out a factor of y on the top from the last bracket, and factorise the first bracket on the bottom:
$\displaystyle = \frac{y(x^2 - y^2 - 2x - 2y)(x - 3y)}{(x - 3y)(x + y)(y - x + 2)}$
Cancel the $\displaystyle (x - 3y)$ term which appears on both the top and bottom:
$\displaystyle = \frac{y(x^2 - y^2 - 2x - 2y)}{(x + y)(y - x + 2)}$
Expand the brackets on the bottom:
$\displaystyle = \frac{y(x^2 - y^2 - 2x - 2y)}{-x^2 + y^2 + 2x + 2y}$
Take out a factor of $\displaystyle -1$ on the bottom:
$\displaystyle = \frac{y(x^2 - y^2 - 2x - 2y)}{-(x^2 - y^2 - 2x - 2y)}$
Now cancel the term $\displaystyle (x^2 - y^2 - 2x - 2y)$ which appears on the top and bottom of the fraction:
$\displaystyle = \frac{y}{-1} = -y$
Hello, Supaweak!
Another approach . . .
Simplify: .$\displaystyle \frac{(x^2-y^2-2x-2y)\cdot(xy-3y^2)}{(x^2-2xy-3y^2)\cdot(y-x+2)}$
Factor each expression . . .
. . $\displaystyle x^2-y^2 - 2x - 2y \:=\:(x-y)(x+y) - 2(x+y) \:=\:(x+y)(x-y-2)$
. . $\displaystyle xy-3y^2 \:=\:y(x-3y)$
. . $\displaystyle x^2-2xy - 3y^2 \:=\:(x+t)(x-3y)$
. . $\displaystyle y - x + 2 \:=\:-(x-y-2)$
The problem becomes: .$\displaystyle \frac{(x+y)(x-y-2)\cdot y(x-3y)}{(x+y)(x-3y) \cdot -(x-y-2)}$
Reduce: . $\displaystyle \frac{{\color{blue}\rlap{//////}}(x+y){\color{red}\rlap{/////////}}(x-y-2)\cdot y{\color{green}\rlap{///////}}(x-3y)}{{\color{blue}\rlap{//////}}(x+y){\color{green}\rlap{///////}}(x-3y) \cdot -{\color{red}\rlap{/////////}}(x-y-2)} \;=\;\frac{y}{\text{-}1} \;=\;\boxed{-y}$